Modern Approaches to Obesity Treatment – literature review - Romaniuk, Mateusz; Wachowska, Maria; Sowiński, Wojciech; Rycąbel, Paweł Maciej; Szymura, Marta; Molenda, Marek Jarosław; Woszczyńska, Oliwia; Wojciechowska, Agnieszka Ewelina; krawczyk, Michał; Paniak, Mateusz (Quality in Sport, 2025)
Abstract Introduction and Purpose: Obesity constitutes a complex health issue of an epidemiological nature, affecting an increasing number of individuals globally. It is associated with numerous health complications, including cardiovascular diseases, type 2 diabetes, hypertension, as well as mental health disorders and a reduced quality of life. The treatment of obesity is a multifaceted process that should encompass lifestyle modifications such as dietary improvement, enhanced physical activity, and psychological support. In certain cases—depending on the severity of obesity and the presence of comorbid conditions—it may become necessary to implement pharmacotherapy or surgical interventions, such as bariatric procedures. This article provides a comprehensive overview of the condition of obesity and its underlying causes. Furthermore, the epidemiology of the phenomenon is presented. The primary focus, however, is placed on the available pharmacological solutions that may assist in combating obesity. Summary: At present, alongside the modification of dietary habits and the enhancement of physical activity, the use of pharmacological agents is becoming an increasingly significant component of obesity therapy. These medications primarily contribute to the reduction of appetite and the limitation of fat absorption, thereby supporting the overall effectiveness of the treatment process.